Cultural and perception dimensions of faecal waste applications for sustainable reuse in Ogun State, Nigeria - Olapeju, O. O. (Italian Association of Chemical Engineering - AIDIC, 2019)
The generationof biogas from faecal wastes currently offers limited economic and environmental benefits to low-income households. The production of biochar from faecal waste is a sustainable alternative to firewood to replace charcoal that is widely utilised for cooking in households in Nigeria. Similarly, biochar production from faecal wastes presents a clean and renewable alternative approachfor creating value from faecal waste. Furthermore, this presents cost-effective recovery, containment, and management of faecal waste. Therefore, the objective of this study is to investigate the existing faecal waste management practices by households in Ogun State, Nigeria. It will also examine perceptions of households to faecal waste as a valuable resource, in either its raw or processed form for energy applications. Based on the multi-stage sampling approach, a total of 165 questionnaires were administered to representative households in the study area. Consequently, a total of 55, 50, and 60 questionnaires were administered in Surulere, Ilaro I, and Sodeke/Sale‐Ijeun I, in the ratio 1.1:1.0:1.23.The selected criteria reflect the variance in the populations of 1,250,435 (33 %), 1,112,761 (30 %), and 1,387,944 (37 %) for Ogun East, Ogun West, and Ogun Central.The study revealed that the most important reason for the prevalence of unsustainable non-recovery faecal waste management in the study area is the perception that households could be exposed to danger as recovered sludge could be used for fetish purpose. Furthermore, at p=0.00, knowledge of faecal waste reuse expressed by respondents strongly associated with their choice of faecal waste emptying method. Lastly, adequate awareness of good sanitation practices and the economic gains of recovering and reusing faecal waste in households requires sustainable enforcement in Nigeria.